Autoestima y habilidades comunicativas en estudiantes del cuarto ciclo de primaria de la Institución Educativa Remanente de Dios, Iquitos 2023 - Matheus Ochoa, Winny Key (2025)
This study examines the relationship between self-esteem and the development of communication skills in fourth grade students. Using a non-experimental quantitative and descriptive correlational design. Data from 171 students were analyzed. The sample used was 100% of the total population. The survey technique was applied and questionnaires were used as instruments. The results reveal that self-esteem is regular and communicative skills are in the process of development. The application of Kendall's Tau-b coefficient confirmed a significant relationship between both variables (p < 0.01), supporting the hypothesis that self-esteem improves communication skills.